The effect of adenoidectomy on transnasal airflow in children with hypertrophy of adenoid tissue - Jan Sojak; Peter Durdik; Renata Pecova (Wolters Kluwer Medknow Publications, 2018)
Background: The aim of this study was to clarify changes of transnasal airflow resulting from adenoidectomy and to assess the effect of surgery depending on adenoid hypertrophy (AH) obstruction grade. Materials and Methods: Altogether fifty children having symptoms of nasal obstruction and adenoids were submitted to a rhinomanometric assessment before and after adenoidectomy. At the same time, using the nasal fiberoptic endoscopy, the grade of AH obstruction was determined, according to which the children were divided into four classes. We assessed the change of total transnasal inspiratory airflow and total nasal resistance due to adenoidectomy. Results: Values of transnasal airflow and nasal resistance measured in the study group of fifty children were preoperatively 262 mL/s and 0.565 kPa/L/s; postoperatively 288 mL/s and 0.52 kPa/L/s. We have noticed statistically significant increase of the airflow (P = 0.015); however, decrease of the resistance (P = 0.054) was not significant. In the group of children suffering from the 1st to 2nd grade (29 children) preoperatively measured values presented 280 mL/s and 0.52 kPa/L/s; postoperatively, 276 mL/s and 0.54 kPa/L/s; change of the airflow (P = 0.634) and resistance (P = 0.829) was not significant. In the study group having the 3rd and 4th grade (21 children), the values indicated preoperatively 240 mL/s and 0.62 kPa/L/s; postoperatively, 340 mL/s and 0.44 kPa/L/s; there were significant airflow increase (P = 0.012) and resistance decrease (P = 0.033). Conclusions: Adenoidectomy significantly increased the airflow; however, we observed the different effect in the group of children with the 1st and 2nd grade compared to the group with the 3rd and 4th grade. A significant increase of the airflow and decrease of the resistance were present only in the group with the 3rd and 4th grade; therefore, the significant reduction of nasal obstruction symptoms might be expected only in this group of patients.